2011
DOI: 10.1590/s0102-311x2011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Vacinação contra influenza em idosos: prevalência, fatores associados e motivos da não-adesão em Campinas, São Paulo, Brasil

Abstract: The objective of this study was to assess the prevalence of self-reported influenza vaccination in the elderly, identifying associated factors and reasons for noncompliance, using a cross-sectional population-based design with stratified two-stage cluster sampling in Campinas, São Paulo State, Brazil, in 2008 IntroduçãoOs benefícios da vacinação contra influenza entre idosos e portadores de condições crônicas têm sido evidenciados em vários estudos 1,2,3,4,5 , mas mesmo diante da recomendação formal para vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
3
61

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(106 citation statements)
references
References 20 publications
7
35
3
61
Order By: Relevance
“…Study conducted among elderly people living in the municipality of southeastern Brazil observed greater acceptance of influenza vaccination among the oldest individuals (12) , differing from the present investigation, in which the younger elderly (60-65 years) had higher rates of vaccination. This result can be explained by the specificity of this age group, they are usually more active and has less limiting diseases (22) , which may interfere with spontaneous seeking for health services.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Study conducted among elderly people living in the municipality of southeastern Brazil observed greater acceptance of influenza vaccination among the oldest individuals (12) , differing from the present investigation, in which the younger elderly (60-65 years) had higher rates of vaccination. This result can be explained by the specificity of this age group, they are usually more active and has less limiting diseases (22) , which may interfere with spontaneous seeking for health services.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were seen for seasonal influenza vaccine in a study performed with the elderly in Campinas (SP, Brazil), in which diabetes and hypertension were associated with vaccination (12) . Distinctively, a study conducted in Poland showed that chronic conditions have given cause for no adherence (23) .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The city reached 70% coverage that year, decreasing in subsequent years (57.1% in 1999, 58. Several studies have shown a significant relationship between age, physical exercise, and comorbidities and influenza vaccine uptake 9,10,11,12,13,14 . However, given the variation in vaccination coverage between regions of Brazil, during each vaccination period studies on factors associated with vaccine uptake have become important tools for guiding interventions to expand coverage and improve protection for this population.…”
Section: Introductionmentioning
confidence: 99%